2010
DOI: 10.1159/000322250
|View full text |Cite
|
Sign up to set email alerts
|

Comet-Tail-Like Inflammatory Infiltrate to Polymer Filaments Develops in Tension-Free Conditions

Abstract: Background: Mesh reinforcement in hiatal hernia repair becomes more frequent but is charged by complications such as erosion or stenosis of the oesophagus. These complications are accompanied by an intense inflammatory infiltrate around the polymer fibres. To characterize this effect, the response to polypropylene fibres in the absence of tension was examined. Methods: In rats, polypropylene sutures (USP size 1, 3-0 and 7-0) were placed in the subcutis of the abdominal wall without knot or tension. On postoper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 70 publications
2
19
0
Order By: Relevance
“…We evaluated the extent and the cellular quality of foreign body granuloma and the CTI. This phenomenon was described in 2002 by Hoer et al [20], and other studies identified the CTI as a tool to investigate the reaction of the host tissue to the surface of the foreign body itself even under tension-free conditions [10]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We evaluated the extent and the cellular quality of foreign body granuloma and the CTI. This phenomenon was described in 2002 by Hoer et al [20], and other studies identified the CTI as a tool to investigate the reaction of the host tissue to the surface of the foreign body itself even under tension-free conditions [10]. …”
Section: Discussionmentioning
confidence: 99%
“…Three different suture materials of 2 cm length were randomized and were placed subcutaneously by puncture of the abdominal wall (n = 15 for each suture) like previously described by Klink et al [10]. After 3, 7 or 21 days (n = 5 for each suture), the animals were euthanized using a lethal dose of pentobarbital sodium (Narcoren®, Rhône Merieux, Laupheim).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to TNM, the expression of several proteins involved in tumour genesis, particularly Gas6, and the number of infiltrating macrophages (CD68) were analysed. In addition, the proteins Notch 3, MMP2 and COX2, were researched to confirm their roles during chronic inflammation and foreign body responses [12]. Each variable was analyzed individually for its prognostic value and subjected to multiple Cox regression analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of a more severe host response, leading to an excessive inflammatory and fibrotic response, could lead to more complications . A first indicator for this host response is the general composition and size of the foreign body granuloma surrounding the biomaterial . The granuloma is a cellular infiltrate of mainly macrophages directly surrounding the material and a fibrotic capsule separating the material from the host with elongated comet‐tail like infiltrates running parallel to the skin and muscle .…”
Section: Discussionmentioning
confidence: 99%